2002
DOI: 10.1079/ber2001143
|View full text |Cite
|
Sign up to set email alerts
|

Can larvae of the pod-borer, Helicoverpa armigera (Lepidoptera: Noctuidae), select between wild and cultivated pigeonpea Cajanus sp. (Fabaceae)?

Abstract: Experiments were conducted to observe the feeding and food selection-behaviour of different instars of the pod-borer Helicoverpa armigera (Hübner) in response to choices between the cultivated and a wild species of Cajanus. First and second instars fed upon a cultivated variety of Cajanus cajan in preference to a wild species, C. scarabaeoides and on flowers of C. cajan, rather than pods or leaves of C. cajan. First and second instars preferred pods of C. scarabaeoides with trichomes removed to pods with trich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As larvae develop, flowering pigeonpea plants develop contemporaneously. Other studies have indicated that larvae ‘switch’ feeding from flowers to pods [ 20 , 22 ]. However, rather than a ‘switch’, this phenomenon might be better thought of as an increased capacity of H. armigera larvae to feed on a range of structures as they develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As larvae develop, flowering pigeonpea plants develop contemporaneously. Other studies have indicated that larvae ‘switch’ feeding from flowers to pods [ 20 , 22 ]. However, rather than a ‘switch’, this phenomenon might be better thought of as an increased capacity of H. armigera larvae to feed on a range of structures as they develop.…”
Section: Discussionmentioning
confidence: 99%
“…Moths are highly attracted to flowering pigeonpea [ 18 , 19 ]. Larvae may feed on pigeonpea plants throughout vegetative and reproductive plant phenological stages [ 13 ], but when provided with a choice, early instars avoid leaves and prefer to feed on flowers [ 18 , 19 , 20 , 21 ]. As larvae develop into larger instars ( Figure 2 ), they ‘switch’ to feeding on pods [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moths are attracted to pigeon pea volatiles ( Rajapakse et al 2006 ), and eggs are then mostly oviposited on floral structures, sites wherein larvae establish ( Rajapakse and Walter 2007 , Volp et al 2023 ). As larvae develop, they are purported to “switch” to feeding on pods, where they can cause substantial yield loss ( Green et al 2002 , Rajapakse 2007 ). Flowers likely play an important role in pigeon pea susceptibility to H. armigera , but the influence of the pigeon pea plant stage on oviposition and establishment of this species is not fully understood.…”
Section: Introductionmentioning
confidence: 99%